Redesign of the Baharoeddin Siregar Stadium with Green Open Space in the Context of Community Life Style in Lubuk Pakam - Sembiring, Sri Gunana; Sumantri , Budi Tri (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Rapid population growth in urban areas causes uncontrolled residential development in cities and the need for infrastructure growth which can have a negative impact on the environment. Based on BPS data analysis, Deli Serdang Regency in 2022 reached 1,953,986 people. The need for space in urban areas is increasing because of this. This results in an increasingly high need for organizations which has an impact on decreasing the quality of the ecological functions of the urban environment, one of which is green open space. Therefore, it is necessary to design stadium infrastructure to support sports activities and provide green open space, especially in Lubuk Pakam City, by paying attention to the ecology and ecological environment. The aim of this research is to formulate a stadium design concept using an urban design architectural approach that blends with the landscape. The research method that will be used is a qualitative method which involves the problem identification stage, literature study, and observation of related designs to collect relevant data. This data is then analyzed to produce a design concept that will be implemented in designing a stadium. The concept resulting from this research will produce aspects such as space circulation, layout, physical design, material selection, building structure and utilities that will be adapted to the community. Through an urban design architectural approach, the stadium design is expected to be able to meet the needs of community activities and parks through infrastructure development that is integrated with green open spaces.